Gut microbiota-derived SCFAs and MetS-related nephropathy - Tian, Xiaofang; Sun, Li; Guo, Shengjie; Yuan, Liying; Zhang, Tang; Huang, Chengqian; He, Tingting; Jiang, Qianfeng; Zeng, Yizhou (Frontiers in Nutrition, 2025)
Metabolic syndrome (MetS) is a group of complex disorders characterized by abnormalities in the metabolism of proteins, fats, carbohydrates, and other substances in the human body. The kidney plays a vital role in these metabolic processes. Similarly, metabolic disorders can lead to renal damage, which can affect both its structure and function. The human intestinal tract possesses an abundant and diverse gut microbial community that significantly influences the physiology and pathology of the host. Growing evidence suggests that gut microbiota-derived metabolites exhibit multiple effects (anti-inflammatory, antioxidant, and improvement of lipid metabolism) in MetS. Particularly, considerable research has suggested that gut microbiota-derived short-chain fatty acids (SCFAs) have an intimate relationship with MetS-related nephropathy. The functions of SCFAs are involved in modulating energy metabolism, regulating immune and inflammatory responses, and inhibiting oxidative stress and mitochondrial damage, which are mainly through the activation of transmembrane G protein-coupled receptors (GPRs) and the inhibition of Histone deacetylase activity (HDAC). Regarding MetS-related nephropathy, therapeutic studies of SCFAs have been conducted in both clinical investigations and animal experiments. However, the role of SCFAs in kidney damage caused by various metabolic disorders has not been fully elucidated. The aim of this article is to review the role of SCFAs in MetS-related nephropathy, which will provide a prospective therapy strategy for MetS-related nephropathy.